A STUDY OF MUKIM CUSTOMARY FORESTS RECOGNITION IN PIDIE REGENCY, ACEH PROVINCE, INDONESIA - Teuku Muttaqin Mansur; Sulaiman Sulaiman; Muazzin Muazzin; M Adli Abdullah; M Jafar M Jafar; Aufa Miranti; Anggun Mareta (Universitas Syiah Kuala, 2023)
This article examines whether mukim customary law communities are entitled to control customary forests, without conflicting with existing villages, while customary forests have traditionally been controlled by mukim and their customary law communities in Pidie Regency Aceh Province, Indonesia. The government has not recognized the proposed mukim forest as it potentially leads to conflict between customary institutions. This study describes such a dynamic for better understanding and finding a way to future solutions. The customary forest proposal by the Mukim has yet to receive formal government recognition. This study used socio-legal research methods. Data was obtained through observations and interviews with imuem mukim, traditional leaders in several mukims, i.e. Paloh mukim, Kunyet Mukim, and Beungga Mukim, in Pidie Regency. This article showed that the recognition of mukim customary forests in Pidie Regency has not received formal recognition from the government. Therefore, new efforts to propose the recognition of mukim as a Customary Law Community known as Masyarakat Hukum Adat/MHA) especially in Pidie Regency needs to be done by all stakeholders.